2006
DOI: 10.1590/s0104-11692006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Identificação dos critérios de avaliação de resultados do serviço de enfermagem nos programas de acreditação hospitalar

Abstract: The quality is already a part of daily reality in hospital organizations. Care is assessed through the organizational structures, work processes and obtained results. The goal was to identify the result evaluation criteria applied to the nursing service, used in accreditation programs, and to classify them in administrative, care and teaching/research activities. We carried out an exploratory, descriptive and quantitative study. Data were collected from 7 companies accredited by the National Accrediting Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
16

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 2 publications
1
5
0
16
Order By: Relevance
“…We agree with the study (6) which concludes that nursing needs to be evaluated in its quantitative and qualitative aspects for a more precise measurement of the quality of care provided to the patient. The same study also highlights the shortage of bibliographies on the evaluation of health systems, were used in a previous study (8) and are systematically measured by the hospitals that constitute the Hospital…”
Section: Introductionsupporting
confidence: 85%
“…We agree with the study (6) which concludes that nursing needs to be evaluated in its quantitative and qualitative aspects for a more precise measurement of the quality of care provided to the patient. The same study also highlights the shortage of bibliographies on the evaluation of health systems, were used in a previous study (8) and are systematically measured by the hospitals that constitute the Hospital…”
Section: Introductionsupporting
confidence: 85%
“…However, there are a paucity of studies on evaluation of health services, specifically on care outcomes and outcome indicators for quality assessment, especially of nursing services (14) .…”
Section: Discussionmentioning
confidence: 99%
“…In both studies identified, the elements involved in the hospital accreditation process are addressed, [27][28] with the ONA methodology being suggested as reference for nursing actions in an Emergency unit. 27 In another study, on the analysis of institutions already certified by the ONA, the indicators/criteria applied to the performance of nursing services are identified.…”
Section: Work Organization and Hospital Accreditationmentioning
confidence: 99%
“…Of the 24 criteria/ indicators identified, 13 are classified as administrative, six as related to care and five as regarding teaching and research. 28 …”
Section: Work Organization and Hospital Accreditationmentioning
confidence: 99%